Activity-Based Protein Profiling in Vivo Using a Copper(I)-Catalyzed Azide-Alkyne [3 + 2] Cycloaddition - Speers, Anna E; Adam, Gregory C; Cravatt, Benjamin F (Journal of the American Chemical Society, 2003)
Toward the goal of assigning function to the tens of thousands of protein products encoded by eukaryotic and prokaryotic genomes, the field of proteomics requires new technologies that can functionally characterize proteins within the dynamic environment of the cell, where these biomolecules are subject to myriad posttranslational modifications and the actions of endogenous activators and inhibitors. Here, we report an advanced strategy for activity-based protein profiling (ABPP) that addresses this important need. We show that several enzymes can be labeled in an activity-based manner both in vitro and in vivo by an azido-sulfonate ester probe and that these labeling events can be detected in whole proteomes by copper-catalyzed ligation with a rhodamine-alkyne reagent. This click chemistry-based strategy for ABPP represents a unique and versatile method for functional proteome analysis.